Pengaruh Kualitas Produk dan Harga terhadap Loyalitas Pelanggan Pengguna Handphone Merek Samsung - Fauzi Ahmad Alhamid (CV. Strata Persada Academia, 2023)
Developments and advances in technology that are increasingly global have an impact on the business world. Samsung as a mobile phone manufacturer will never stop to continue to improve product quality and compete at affordable prices. This study aims to describe the effect of product quality and price on customer loyalty of Samsung brand mobile phone users. The sampling technique used probability sampling technique as many as 30 people. The data collection instrument used questionnaires while the scale used was a Likert scale. Methods of data analysis using multiple linear regression. The results showed that partially the product quality and price variables had a significant effect on customer loyalty. Simultaneously the product quality and price variables significantly influence customer loyalty with a probability level of <0.05.